Goodbye, Eastern Europe : an intimate history of a divided land - Mikanowski, Jacob (Pantheon Books, 2023)
"In light of Russia's aggressive 2022 invasion of Ukraine, Goodbye, Eastern Europe is a crucial, elucidative read, a sweeping epic chronicling a thousand years of strife, war, and bloodshed--from pre-Christianity to the fall of Communism--illuminating the remarkable cultural significance and richness of a place perpetually lost to the margins of history. Eastern Europe, the moniker, has gone out of fashion since the fall of the Soviet Union. Ask someone now, and they might tell you that Estonia is in the Baltics, or Scandinavia, that Slovakia is in Central Europe and Croatia is in the Eastern Adriatic or the Balkans. In fact, Eastern Europe is a place that barely exists at all, except in cultural memory. Yet it remains a powerful marker of identity for many, with a fragmented and wide history, defined by texts, myths, and memories of centuries of hardship and suffering. Goodbye, Eastern Europe is a masterful narrative about a place that has survived the brink of being forgotten. Beginning with long-lost accounts of early pagan life, Mikanowski offers a kaleidoscopic tour recounting the rise and fall of the great empires--Ottoman, Hapsburg, and Russian--the dawn of the modern era, the ravages of Fascism and Communism, as well as Capitalism, the birth of the modern nation-state, and more. A student of literature, history, and the ghosts of his own family's past, Mikanowski paints a magisterial portrait of a place united by diversity, and eclecticism, and a people with the shared story of being the dominated rather than the dominating. The result is a loving and ebullient celebration of the distinctive and vibrant cultures that stubbornly persisted at the margins of Western Europe, and a powerful corrective that re-centers our understanding of how the modern Western world took shape"--